Quality Control Analysis on Steel Construction Projects Using the Method Statistical Quality Control and Failure Mode and Effects Analysis - Kholidah Zilfianah; Elly Ismiyah; Akhmad Wasiur Rizqi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
XYZ is a steel fabrication company. It have some business such as; Storage, Crosstube, Steel Structure for pre-heater, Bulk Storage bagging unit and etc. Crosstube produce with a high failure rate, it was 212/2185 defective products. This research goal is to analyse quality control at PT. XYZ from June 2021 to May 2022 using Statistical Quality Control and Failure Mode and Effects Analysis. By using pareto diagram it found that a defect occur during welding process, which is 47% more dominant on the type of product defect. It was realize the RPN value of each process are; 1430 for the welding process, 1748 for drilling process, and 1470 for cutting process. Action that should be taken by PT. XYZ is using statistic method. It is to find out the category that caused product failure. Furthermore, PT. XYZ need to make a Standard Operational Procedure to minimized failure in the production process. PT. XYZ adalah perusahaan manufaktur fabrikasi baja, bidang usaha jasa yang dijalankannya yaitu Limestone Storage, Crosstube, Steel Structure for Pre-Heater, Bulk Storage Bagging Unit dan lain – lain. Di antara usaha tersebut, Crosstube menjadi produk dengan tingkat kegagalan yang tinggi saat proses produksi, terdapat 212 produk cacat dari 2185 produk yang dihasilkan. Penelitian ini bertujuan untuk menganalisis pengendalian kualitas pada produk PT. XYZ pada bulan Juni 2021-Mei 2022 dengan metode Statistical Quality Control dan Failure Mode and Effects Analysis. Terungkap pada diagram pareto bahwa kecacatan saat melakukan proses las sebesar 47% lebih dominan pada jenis kerusakan produk. RPN pada setiap proses sebesar 1403 pada proses las, 1748 proses bor, 1470 proses cutting. Tindakan yang harus dilakukan oleh PT. XYZ yaitu menggunakan metode statistik untuk dapat mengetahui kategori apa yang menyebabkan terjadinya kegagalan produk. Selain itu PT. XYZ perlu membuat Standard Operasional Prosedure untuk menghindari peningkatan kegagalan produk.